2013
DOI: 10.1007/s00246-013-0688-2
|View full text |Cite
|
Sign up to set email alerts
|

Food and Drug Administration (FDA) Postmarket Reported Side Effects and Adverse Events Associated with Pulmonary Hypertension Therapy in Pediatric Patients

Abstract: Because most medications for pediatric pulmonary hypertension (PH) are used off label and based on adult trials, little information is available on pediatric-specific adverse events (AEs). Although drug manufacturers are required to submit postmarket AE reports to the Food and Drug Administration (FDA), this information is rarely transmitted to practitioners. In the setting of a recent FDA warning for sildenafil, the authors sought to give a better description of the AEs associated with current therapies in pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 4 publications
1
22
0
Order By: Relevance
“…It will be very important to study short- and long-term adverse effects, dosages, and timing on the fetus and pregnant women before starting sildenafil clinically, including pulmonary, cardiac, vascular, visual, and neurologic evaluations [28]. Recently, Luong et al [16] showed that antenatal sildenafil had no adverse effects on retinal and brain development.…”
Section: Discussionmentioning
confidence: 99%
“…It will be very important to study short- and long-term adverse effects, dosages, and timing on the fetus and pregnant women before starting sildenafil clinically, including pulmonary, cardiac, vascular, visual, and neurologic evaluations [28]. Recently, Luong et al [16] showed that antenatal sildenafil had no adverse effects on retinal and brain development.…”
Section: Discussionmentioning
confidence: 99%
“…7 That is, when healthy male subjects received 40 mg tadalafil once a day concomitantly with bosentan at a dose of 125 mg twice a day, the mean area under the curve values of tadalafil after 10 days of repetitive dose decreased by 41.5% compared with tadalafil alone. 7 Because bosentan is frequently coadministered with PDE5 inhibitors in the treatment of children with PAH, 3,5,11 this drug-drug interaction should be of interest to most pediatricians. In addition, it was reported that gender, age, and hepatic impairment have no effect on the pharmacokinetics of tadalafil in adults, although systemic exposure in the elderly was 25% greater than in young subjects.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 The clinical development of new agents has improved the quality of life and mortality of patients with PAH in the past 2 decades. 3 One such drug class is phosphodiesterase type-5 (PDE5) inhibitors (sildenafil and tadalafil), and this class of therapy has contributed to the improved prognosis of adult PAH patients. 2,3 On the other hand, no therapies are approved for children.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…66 The 3 most frequent adverse events were liver dysfunction (62%), cardiac failure (11%), and syncope (8.6%) for bosentan; pulmonary hemorrhage (13.1%), cardiac failure (9.7%), and hemoptysis (8%) for epoprostenol; and cardiac failure (12.4%), hypotension (11.2%), and dyspnea (10.1%) for sildenafil. Serious adverse events not previously reported in the literature (eg, pulmonary hemorrhage, hemoptysis, pneumonia, cardiac arrest, hypoxia) were also reported.…”
Section: Disclosuresmentioning
confidence: 99%